2010
DOI: 10.1002/uog.8660
|View full text |Cite
|
Sign up to set email alerts
|

P25.13: Case report of spinal dysraphism with lemon and banana signs in the second trimester and normal intracranial translucency in the first trimester

Abstract: Poster abstracts different occasions (intraobserver variability) or between different examiners (interobserver variability) was calculated by using intraclass correlation coefficient (ICC) and Bland-Altman graphs. Results: It was observed high intra-and interobserver agreement with ICC > 0.90 for all 3D power Doppler indices in the ACA territory. Intraobserver reliability: VI [ICC = 0.984 (CI 95% 0.959-0.994)], FI [ICC = 0.985 (CI 95% 0.962-0.994)], VFI [ICC = 0.986 (CI 95% 0.964-0.994)]. Interobserver reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Hence, there is a growing body of literature providing evidence that the presence of the IT does not exclude a neural tube defect. Among others, Hynek et al [11] and Arigita et al [12] reported cases with open spina bifida where the IT was normal at 13 weeks of gestation. In the most recent study published on first trimester screening for open spina bifida, Mangione et al performed a retrospective study on 52 cases with open spina bifida and 208 normal fetuses and found that the absence of the cisterna magna is the best single screening parameter, superior to IT or posterior shift of the brainstem [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is a growing body of literature providing evidence that the presence of the IT does not exclude a neural tube defect. Among others, Hynek et al [11] and Arigita et al [12] reported cases with open spina bifida where the IT was normal at 13 weeks of gestation. In the most recent study published on first trimester screening for open spina bifida, Mangione et al performed a retrospective study on 52 cases with open spina bifida and 208 normal fetuses and found that the absence of the cisterna magna is the best single screening parameter, superior to IT or posterior shift of the brainstem [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the pathophysiologic theories on the development of the Chiari II malformation consider the fourth ventricle a central anatomic structure affected by the neural tube defect. It is conceivable that the fourth ventricle is not always obliterated in first‐trimester fetuses with spina bifida, as was observed by other authors as well 2 , 3 . Considering the small number of first‐trimester spina bifida cases in the study by Chaoui et al 1 and in our own, it is possible that study patients were truly anatomically discrepant with respect to fourth ventricle obliteration by chance, thereby skewing the observed efficacy of this marker.…”
Section: Discussionmentioning
confidence: 44%
“…We performed a retrospective analysis of 250 first‐trimester sonographic examinations, consisting of 245 healthy fetuses and 5 fetuses with spina bifida. Images had been acquired in the process of nuchal translucency screening at Cedars‐Sinai Medical Center, in concordance with the guidelines of the Fetal Medicine Foundation 3 , 4 . The gestational ages ranged between 11 weeks and 13 weeks 6 days, consistent with a range of crown‐rump lengths between 45 and 83 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation